OPTIMALISASI JUMLAH PRODUKSI TIPE RUMAH PADA PROYEK PENGEMBANG PERUMAHAN DENGAN MENGGUNAKAN METODE SIMPLEK (STUDI KASUS : PT. ARAYA BUMI MEGAH MALANG) - Utari, Rini Febri; Saiful Amal, Andi (Media Teknik Sipil, 2012)
Rini Febri Utari1 & Andi SA21&2Jurusan Teknik Sipil Fakultas Teknik Universitas Muhammadiyah MalangAlamat Korespondensi : Jalan Raya Tlogomas 246 Malang 65144email :rynfu_sheara@yahoo.co.idABSTRACTThe need of housing in Indonesia is estimated annually by an average of 800,000 new housingunits per year, the state saw a lot of developers that have sprung up to provide homes. But thechallenges that are often faced by the housing developers is to formulate the type of house that willbe produced so that it meets the constraints like aspects of the market, the area, production costs,comply with government regulations as well as the maximum profit margin. The purpose of thisstudy is to formulate the composition of the type of house to be built so as to achieve the optimumsolution and maximum profit.Optimization method used is the simplex method. As the object of study is the housing ArayaBumi Megah Malang, especially Cluster GreenWood Golf with a land area of 100.000m2. Type ofhouse that will be built is the type X1 (45/130) with Rp.389.750.000 price per unit, type X2 (54/170)with Rp.505.200.000 price per unit , the type of X3 (61/162) at a price of Rp.514.200.000 per unit,type X4 (65/144) with Rp.550.500.000 price per unit, type X5 (77/162) with Rp.609.500.000 priceper unit, type X6 (96/180) at a price Rp.720.500.000 per unit, the type X7 (141/144) withRp.833.100.000 price per unit, type X8 (161/162) with Rp.918.625.000 price per unit , the type ofX9 (221/200) with Rp.1.148.500.000 price per unit and the type X10 (308/375) at a price per unitRp.1.654.500.000. Function objective of this research is to gain maximum restriction function island area, limits cost of production and the market demand aspect.The analysis showed that the optimum combination type number built is X1=0, X2=0, X3=0,X4=387, X5=0 , X6=99 , X7=95 X8=0 X9=64 X10=0. So that from the ten types offered are only fourtypes produced the type X4 (65/144) of 387 units, type X6 (96/180) by 99 units, the type X7 (141/144) 95 units and the type of X9 (221/200) by 64 units to obtain the maximum profit ofRp.78.483.073.000.Key words : Optimization , Simplex Method , Number of housing types